Multi-Material Topology Optimization Taking into Account the Position of Material Interfaces in 3D - Robert Renz; Niklas Frank; Albert Albers (Applied Sciences, 2025)
Multi-material design as a method of lightweight construction enables the targeted use of materials in a component by utilizing the individual material properties. However, this advantage comes with additional challenges for the product developer, such as the increased effort involved in identifying the design. Multi-material topology optimization is a method that can support the product developer in creating initial weight-optimized component designs in multi-material design in early phases. In addition, several state-of-the-art studies show that the position of the interfaces between the materials has an influence on the strength of the optimization result. These investigations took place in 2D and developed optimization methods which largely use non-linear building blocks, such as cohesive behavior. The non-linear components lead to an increase in computational effort and a reduction in the robustness of the optimization. In this article, a method for the consideration of adhesive-bonded interfaces in multi-material topology optimization in 3D by means of an objective function is developed. For this purpose, requirements are derived based on an analysis of the different load cases of a bond and these are used to create the method. The method is then successfully validated by means of two numerical experiments. In addition, the influence of a newly introduced parameter on the optimization results is investigated by means of a parameter study.